Power quality enhancement by using D-FACTS systems applied to distributed generation - Si Zegnoun Ahmed; Mohammed Nasser Tandjaoui; Mokhtar Djebbar; Chellali Benachaiba; B. Mazari (Institute of Advanced Engineering and Science, 2019)
In the majority of the isolated areas, the diesel generator is the principal source of electric power. For these areas, the price of extension of the electrical supply network is prohibitory and the price of fuel increases radically with insulation. The continuous fall in the prices of the generators based on renewable energy and the increasing reliability of these systems led to a greater use of the sources of renewable energy for the generation of electric power in the isolated areas. The diesel generators can incorporate in a network with other sources in base of renewable energies in order to create a new network known as distributed network. More recently intermittent renewable resources such as the wind power were considered as a distributed generation which is seen as being deployed to reduce the total emissions. The distributed generation equipment sets causing electric disturbances result in destabilizing the global network as well as pollutant, for these reason, system D-FACTS comes to answer all the concern of the customers, manufacturers, suppliers and the managers of the distributed network.